TRANSFORMING ARABIYA BAINA YADAIK LEARNING: GROUP AND INDIVIDUAL REMEDIAL STRATEGIES FOR ACADEMIC ACHIEVEMENT - Arifdo Putra; Mahyudin Ritonga; Rahmawati Rahmawati (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
The Arabic language learning using the book "Arabiya Baina Yadaik" at Dar El Iman Islamic Boarding School in Padang faces significant challenges in meeting the graduation standard of a minimum score of 85. Among the 21 first-year junior high school students, 52% did not achieve this standard. To address this issue, remedial activities were conducted to ensure all students could meet the learning targets. This research aims to improve Arabic language learning outcomes through a remedial teaching method that combines group and individual tasks. This study employs a qualitative approach with a descriptive method to detail the implementation and results of the remedial activities. Data were collected through observations, interviews, and analysis of student scores before and after the remedial activities. The findings indicate a significant improvement in students' learning outcomes following the remedial activities. The graduation rate increased from 48% to 85%, and the number of students who did not pass decreased from 11 to 3. This demonstrates that the remedial teaching method is effective in helping students achieve the graduation standard. In conclusion, combining group and individual tasks in remedial teaching can significantly enhance students' Arabic learning outcomes and overcome learning obstacles. This research contributes to developing more effective Arabic teaching strategies in Islamic boarding schools and other educational institutions.